2020
DOI: 10.1139/cjfas-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Using temporally explicit habitat suitability models to infer the migratory pattern of a large mobile shark

Abstract: Conservation and management measures for large mobile sharks are more effective when information on migratory patterns and environmental cues are known. In the absence of long-term monitoring data or tracking programs, available information is based on occasional catch/sighting records from a variety of sources, usually constrained in space and time. This study demonstrates the utility of developing temporally explicit habitat suitability (HS) models to infer the migratory pattern of large mobile sharks. Bimon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 107 publications
2
29
0
Order By: Relevance
“…It is noteworthy that the seasonal patterns for N. cepedianus and G. galeus were only statistically significant in the southern study site (CM), since the two species were not recorded in the area during winter. This observation agrees with recent evidence on the migratory pathways for G. galeus (Jaureguizar et al 2018) and N. cepedianus (De Wysiecki et al 2020), characterized by northward displacements during colder months, possibly explaining why they were not found in CM in winter. However, a previous study in CV using fishing technics recorded N. cepedianus year-round, but with marked seasonality in catches (Irigoyen et al 2018).…”
Section: D���������supporting
confidence: 92%
“…It is noteworthy that the seasonal patterns for N. cepedianus and G. galeus were only statistically significant in the southern study site (CM), since the two species were not recorded in the area during winter. This observation agrees with recent evidence on the migratory pathways for G. galeus (Jaureguizar et al 2018) and N. cepedianus (De Wysiecki et al 2020), characterized by northward displacements during colder months, possibly explaining why they were not found in CM in winter. However, a previous study in CV using fishing technics recorded N. cepedianus year-round, but with marked seasonality in catches (Irigoyen et al 2018).…”
Section: D���������supporting
confidence: 92%
“…The current study and previous field observations in southern Argentina support the prediction of spatial suitability models (De Wysiecki et al ., 2020) on the importance of the Rio de la Plata southern boundary for the N. cepedianus population in the SACS. The observed monthly length distribution showed that the mean length of YOY increased throughout the year with the co‐occurrence in the spring of a new (TL < 50 cm) and an older (TL > 110 cm) cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The broadnose sevengill shark, Notorynchus cepedianus (Péron, 1807), is a large top predator in many temperate coastal marine ecosystems of the world (Barnett et al ., 2012). The species, especially juveniles, is increasingly retained as by‐catch in several fisheries worldwide, mostly in commercial and small‐scale gillnet fisheries ( e.g ., southern Australia, Walker et al ., 2005; oceanic coast of Uruguay, Laporta et al ., 2008; northern coast of Argentina, Jaureguizar et al ., 2015, De Wysiecki et al ., 2018) and recreational fishers ( e.g ., southern Africa, Ebert, 1996; Southwest Atlantic, Lucifora et al ., 2005, De Wysiecki et al ., 2020). Globally, N. cepedianus is currently listed as “Vulnerable” by the IUCN.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology and behavior of sevengill sharks are an adaptation to demersal habits across a range of different environments from coastal to shelf waters, and from murky to clear oceanic waters. The swimming capabilities of these sharks are noteworthy as they perform large scale migrations (Barnett et al., 2011; De Wysiecki et al., 2020; Ketchum et al., 2017; Williams et al., 2012). Nevertheless, fine‐scale active tracking revealed that they are typically slow swimmers (average cruise speed 0.50 ± 0.04 m/s) that can exert eventual burst speed motions (up to 6.1 m/s), probably related to predation attempts (Barnett et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…The morphology and behavior of sevengill sharks are an adaptation to demersal habits across a range of different environments from coastal to shelf waters, and from murky to clear oceanic waters. The swimming capabilities of these sharks are noteworthy as they perform large scale migrations (Barnett et al, 2011;De Wysiecki et al, 2020;Ketchum et al, 2017;Williams et al, 2012).…”
Section: Introductionmentioning
confidence: 99%